First-Attempt Intubation Success of Video Laryngoscopy in Patients with Anticipated Difficult Direct Laryngoscopy: A Multicenter Randomized Controlled Trial Comparing the C-MAC D-Blade Versus the GlideScope in a Mixed Provider and Diverse Patient Population. (March 2016) - Aziz, Michael F.; Abrons, Ron O.; Cattano, Davide; Bayman, Emine O.; Swanson, David E.; Hagberg, Carin A.; Todd, Michael M.; Brambrink, Ansgar M.
Abstract : BACKGROUND: Intubation success in patients with predicted difficult airways is improved by video laryngoscopy. In particular, acute-angle video laryngoscopes are now frequently chosen for endotracheal intubation in these patients. However, there is no evidence concerning whether different acute-angle video laryngoscopes can be used interchangeably in this scenario and would allow endotracheal intubation with the same success rate. We therefore tested whether first-attempt intubation success is similar when using a newly introduced acute-angle blade, that is an element of an extended airway management system (C-MAC D-Blade) compared with a well-established acute-angle video laryngoscope (GlideScope). METHODS: In this large multicentered prospective randomized controlled noninferiority trial, patients requiring general anesthesia for elective surgery and presenting with clinical predictors of difficult laryngoscopy were randomly assigned to intubation using either the C-MAC D-Blade or the GlideScope video laryngoscope. The hypothesis was that first-attempt intubation success using the new device (D-Blade) is no >4% less than the established device (GlideScope), which would determine noninferiority of the new instrument versus the established instrument. The secondary outcomes we observed included intubation success with multiple attempts and airway-related complications within 7 days of enrollment. RESULTS: Eleven hundred patients were randomly assigned to either video laryngoscope. Intubation success rate on first attempt was 96.2% in the GlideScope group and 93.4% in the C-MAC D-Blade group. Although the absolute difference between the 2 groups was only 2.8%, the 90.35% upper confidence limit of the difference exceeded the predefined margin (4.98%), indicating a rejection of the noninferiority hypothesis for first-attempt intubation success. For attending anesthesiologists, and upon multiple attempts, intubation success did not differ between systems. Pharyngeal injury was noted in 1% of the patients, and the incidence did not differ between interventional groups. CONCLUSIONS: Head-to-head comparison in this large multicenter trial revealed that the newly introduced C-MAC D-Blade does not yield the same first-attempt intubation success as the GlideScope in patients with predicted difficult laryngoscopy except in the hands of attending anesthesiologists. Additional research would be necessary to identify potential causes for this difference. Intubation success rates were very high with both systems, indicating that acute-angle video laryngoscopy is an exceptionally successful strategy for the initial approach to endotracheal intubation in patients with predicted difficult laryngoscopy. Abstract : Published ahead of print November 17, 2015